2017
DOI: 10.1002/jms.3967
|View full text |Cite
|
Sign up to set email alerts
|

Rapid characterization of chemical constituents of Platycodon grandiflorum and its adulterant Adenophora stricta by UPLC‐QTOF‐MS/MS

Abstract: Platycodon grandiflorum (PG) is extensively used for treating cough, excessive phlegm, sore throat, bronchitis and asthma, whereas Adenophora stricta (AS) is commonly used to reduce phlegm, clear lung and tonify stomach. Due to similar appearances, PG is sometimes adulterated with cheap AS so as to gain profits. And this will inevitably result in different pharmacological property. In order to further clarify the differences in the chemical composition of these two Chinese herbs, the ultra-high performance liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…G. alypum L., it is the first time that shanzhiside methyl ester (peak 15) is described in Plantaginaceae family. However, this iridoid derivative, as well as its fragmentation pattern, has been previously described in the plant kingdom …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…G. alypum L., it is the first time that shanzhiside methyl ester (peak 15) is described in Plantaginaceae family. However, this iridoid derivative, as well as its fragmentation pattern, has been previously described in the plant kingdom …”
Section: Resultsmentioning
confidence: 97%
“…Finally, the last new compound found in G. orientalis and G. trichosantha corresponded to gingerol (peak 107). Its MS/MS spectra showed fragments at m / z 177 and 141 which are related to [M – H – H 2 O – C 6 H 14 O] − and [M – H – C 9 H 13 O 2 ] − , respectively …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has shown that the active compounds from medicinal herbs exert protective effects against nephrotoxicity induced by cisplatin [ 15 ]. The root of Platycodon grandiflorum , a common medicinal and edible plant, contains many active ingredients, such as steroidal saponins, flavonoids, phenolic acids, and sterols, in which the saponins are regarded as the major active compounds [ 16 ]. The root of P. grandiflorum (PG) is widely used in traditional Chinese medicine, which exert hepatoprotective and insulin-sensitizing effects [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As part of these research works, we reported this method to detect some natural products including Platycodon grandiorum and Ginseng root. 21,22 Our research results showed that this method is high throughput, comprehensive, simple and efficient. As far as we know, the UPLC-Q/TOF-MS method has not been reported to identify the components in COT.…”
Section: Introductionmentioning
confidence: 78%